IMPACT OF GENDER DIFFERENCES AND BODY MASS INDEX ON SKIN BIOPHYSICAL PARAMETERS OF CORONAVIRUS PATIENTS - Bari, Dindar S; Salih, Jalal M.; Yacoob Aldosky, Haval Y.; Martinsen, Ørjan G. (Science Journal of University of Zakho, 2024)
Once the pandemic started, there were no clues regarding overall COVID-19 infections. There are no studies that demonstrate the effects of COVID-19 on skin surface pH, moisture, sebum, and temperature in terms of gender differences and body mass index (BMI) among infected people. The goal of this study was to investigate some of the skin biophysical scores of patients infected with COVID-19 and evaluate the impact of gender differences and the body mass index on them. Skin surface sebum, pH, temperature, and hydration (moisture), were measured in 30 COVID-19 patients using employing non-invasive portable devices. Insignificant effects of gender differences and BMI on skin biophysical properties were observed. In addition, females showed higher skin biophysical characteristics than males. Moreover, obese patients had higher skin biophysical parameter values than normal-weight patients. However, all the study results were statistically insignificant (p > 0.05). Further investigations are required to recognize other skin biophysical parameters such as transepidermal water loss and elasticity that may aid in the early identification of skin damage in COVID-19 patients.